OPTIMALISASI MANAJEMEN KEUANGAN: MEMBANGUN KETANGGUHAN DALAM DINAMIKA KOMPLEKS EKONOMI GLOBAL YANG TERKAIT ERAT - Teguh Prakoso (CV. Adiba Aisha Amira, 2024)
Optimizing Financial Management is an important concept in maintaining business stability and resilience in facing increasingly complex and closely linked global economic dynamics. This abstract provides a brief overview of the importance of effective financial management in the context of a changing global economy. Financial resilience is the main focus in facing economic uncertainty, which includes establishing financial reserves, portfolio diversification, and the use of technology and innovation in financial analysis. A deep understanding of the global economy, continuous adaptation and competent leadership are the keys to building the financial resilience required in today's complex business environment. In an era of continuously developing global economy, optimal financial management is not only a necessity, but also the foundation for achieving sustainable growth and resilience.